Isolated anti-SS-B (La) antibodies: rare occurrence and lack of diagnostic value - Xavier Mariette; Gaetane Nocturne; Pascale Chretien; Claire Goulvestre; Paul Cioni; Eric Ballot; Dounia Khelifi-Touhami (RMD Open)
Objective Anti-SS-B antibodies are often associated with anti-SS-A in Sjögren’s disease. Compared to anti-SS-A antibody positivity, the significance of the immunological profile anti-SS-B positive/anti-SS-A negative remains controversial. We aimed to evaluate the prevalence and diagnostic significance of isolated anti-SS-B antibodies.Methods We conducted a retrospective study across three hospitals of the Assistance Publique—Hôpitaux de Paris. Patients with anti-SS-B positivity were identified using ELISA, addressable laser beam immunoassay (ALBIA) and immunodot assays. They were retained if anti-SS-B was positive in two techniques and anti-SS-A was absent. Clinical, biological and immunological data were extracted and presented in a descriptive analysis.Results A total of 80 540 requests for anti-SS-B antibody testing were carried out over a period of 7.9 years. Anti-SS-B positivity was found in 1693 patients. Among them, 335 (19.8%) patients had isolated anti-SS-B in ELISA/ALBIA. Immunodot was performed in 186 of them and confirmed anti-SS-B positivity in 61 patients (3.6% of anti-SS-B positivity). 24 patients (39.3%) presented with a history of various autoimmune or autoinflammatory diseases and only 6 were diagnosed with a new connective tissue disease. After a median follow-up of 26 months, only two new diagnoses were made.Conclusion Anti-SS-B without anti-SS-A is exceedingly rare when accurately identified by a rigorous immunological approach. The initial anti-SS-B positivity does not correlate with a specific condition, both at the time of initial identification and after a 26-month follow-up period. This supports the fact that isolated anti-SS-B has no diagnostic or prognostic value.